2008
DOI: 10.1111/j.1444-0938.2007.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ocular isolates from symptomatic adverse events: antibiotic resistance and similarity of bacteria causing adverse events

Abstract: Background:  Staphylococcus is the leading cause of microbial keratitis. Staphylococcus aureus isolated from ocular infections with resistance to a wide range of antibiotics, including the commonly prescribed fluoroquinolones, is emerging. The aim of this study was to determine the current antibiotic susceptibilities of ocular S. aureus isolates and also determine whether isolates from different adverse events or those with similar antimicrobial susceptibilities are related. Methods:  A collection of 55 S. aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…In the present study, chloramphenicol remained as a good choice of treatment for conjunctivitis and niCIE caused by S. aureus, as 96% and 78% of isolates, respectively, were susceptible. Gram-positive bacteria isolated from microbial keratitis isolates have also been reported regarding low levels of chloramphenicol resistance in the Australian and USA isolates [65,66]. However, the current study findings of the increasing resistance of microbial keratitis strains from Australia [67], isolated between 2006 and 2018, and from the USA (45%), isolated in 2004, are not consistent with these earlier studies and suggest it is a poor choice for treatment of corneal infections.…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, chloramphenicol remained as a good choice of treatment for conjunctivitis and niCIE caused by S. aureus, as 96% and 78% of isolates, respectively, were susceptible. Gram-positive bacteria isolated from microbial keratitis isolates have also been reported regarding low levels of chloramphenicol resistance in the Australian and USA isolates [65,66]. However, the current study findings of the increasing resistance of microbial keratitis strains from Australia [67], isolated between 2006 and 2018, and from the USA (45%), isolated in 2004, are not consistent with these earlier studies and suggest it is a poor choice for treatment of corneal infections.…”
Section: Discussioncontrasting
confidence: 84%
“…A multicenter study examining S. aureus isolated from corneal scrapings in the United States, Australia, and India also showed that 100% of strains were sensitive to vancomycin. 23 The only study to our knowledge with similar rates of vancomycin resistance is from Aravind Eye Hospital in Coimbatore, India. They reported on 35 cases of bacterial keratitis with positive cultures for coagulase-negative Staphylococcus and found that 75% of the 20 strains of S. epidermidis were resistant to vancomycin.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with a previous study from South India that reported a 93.8% sensitivity (95% CI, 92.8-94.7) for gram stain and a 99.1% sensitivity (95% CI, 98.3-99.5) for KOH smear in the detection of microorganisms in cases of suspected infectious keratitis. 23 Thus, smear microscopy is a very important test that provides rapid etiologic information and allows for initiation of the most appropriate antimicrobial therapy at the time of presentation. This is particularly important in developing countries such as Nepal, where follow-up is not always feasible and culture techniques are not always available.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Fluoroquinolone and nonfluoroquinolone resistance has emerged among ocular staphylococci and constitutes a growing management dilemma for ophthalmologists and other healthcare providers. 3,[7][8][9][10] The increasing trend of antibiotic resistance among these common ocular pathogens necessitates the development of new and or novel antibiotics. 11,12 Besifloxacin ophthalmic suspension is a new and unique fluoroquinolone developed specifically for ophthalmic use.…”
Section: Introductionmentioning
confidence: 99%